Quantification and Revolution: An Investigation of German Capital Flight after the First - Christophe Farquet (European Historical Economics Society (EHES), 2019)
It is well known that after the First World War there was a massive flight of capital from the major European countries to foreign financial centres. It is surprising, however, to note that no historian to date has actually taken the trouble to make a detailed study of the phenomenon. The aim of this article is to go beyond the impressionism that characterises the historical approach to the study of capital flight following the First World War. In order to show what can and cannot be established, the subject of study will be Germany. After presenting the main difficulties encountered in quantifying the flight of German capital, the article will go on to provide a new estimate of it. A wide range of sources were referred to for the survey: national archives, expert reports, bank statistics, and balances of payments. The application of rigorous historical method, with crosschecking and critical analysis of documents, have made it possible to establish new relevant facts regarding the flight of German capital following the First World War. The final figure obtained is greater than those generally accepted.
Keywords: F32; G15; H26; N24; N44; Z11; 330; Capital flight; tax havens; interwar period; hyperinflation; Germany; Switzerland